Molecular characterization and antimicrobial resistance patterns of spp. and Escherichia coli of laying chicken - Saifuddin, AKM; Isalm, SKM Azizul; Anwar, Md Nurul (Microbes and Health, 2017)
Multidrug resistant (MDR) Gram-negative bacteria are most the common causes of diseases in commercial poultry, and antibiotic resistance of these organisms is often plasmid mediated. In Bangladesh such types of data are very much scarce. In this study, the antibiogram profile of Salmonella spp and E. coli isolates from 20 either clinically affected or dead laying chicken obtained from 10 commercial layer farms was performed. And MDR pattern was determined by using 7 common antimicrobials followed by isolation of plasmids to correlate between plasmids and drug resistance. Of these tested samples, 70-100% of both Salmonella Spp and E. coli were resistant to ?-lactam antibiotics (ampicillin, amoxicillin, and penicillin) cephalexin and cotrimoxazole while 60-90% isolates of both species were susceptible to both ciprofloxacin and gentamicin. Both Salmonella spp and E. coli isolates contain plasmids above 10 kbp size which might contain MDR genes. This is the first report on the characterization of plasmids found in both Salmonella spp and E. coli isolates obtained from a significant number of commercial layer farms (N=10) in Chittagong District, Bangladesh. The gathered information furthers our understanding of the mechanisms of drug resistance in specific region related to other parts of the country and world. The large plasmids might be potential factors for dissemination of antibiotic resistance genes regionally Microbes and Health, December 2016, 5(1): 4-6